Feasibility and Clinical Outcome of Reboa in Patients with Impending Traumatic Cardiac Arrest. Issue 2 (August 2020) - McGreevy, David Thomas; Abu-Zidan, Fikri M.; Sadeghi, Mitra; Pirouzram, Artai; Toivola, Asko; Skoog, Per; Idoguchi, Koji; Kon, Yuri; Ishida, Tokiya; Matsumura, Yosuke; Matsumoto, Junichi; Reva, Viktor; et al.
ABSTRACT: Background: Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) may improve Systolic Blood Pressure (SBP) in hypovolemic shock. It has, however, not been studied in patients with impending traumatic cardiac arrest (ITCA). We aimed to study the feasibility and clinical outcome of REBOA in patients with ITCA using data from the ABOTrauma Registry. Methods: Retrospective and prospective data on the use of REBOA from 16 centers globally were collected. SBP was measured both at pre- and post-REBOA inflation. Data collected included patients' demography, vascular access technique, number of attempts, catheter size, operator, zone and duration of occlusion, and clinical outcome. Results: There were 74 patients in this high-risk patient group. REBOA was performed on all patients. A 7-10Fr catheter was used in 66.7% and 58.5% were placed on the first attempt, 52.1% through blind insertion and 93.2% inflated in Zone I, 64.8% for a period of 30 to 60 min, 82.1% by ER doctors, trauma surgeons, or vascular surgeons. SBP significantly improved to 90 mm Hg following the inflation of REBOA. 36.6% of the patients survived. Conclusions: Our study has shown that REBOA may be performed in patients with ITCA, SBP can be elevated, and 36.6% of the patients survived if REBOA placement is successful.